A coupled chemo‐viscoplastic cap model for simulating the behavior of hydrating cemented tailings backfill under blast loading. (17th November 2015) - Lu, Gongda; Fall, Mamadou
Summary: Although the use of blasting has become a routine in contemporary mine operations, there is a lack of knowledge on the response of cement tailings backfills subjected to sudden dynamic loading. To rationally describe such a phenomenon, a new coupled chemo‐viscoplastic cap model is proposed in the present study to describe the behavior of hydrating cemented tailings backfill under blast loading. A modified Perzyna type of visco‐plasticity model is adopted to represent the rate‐dependent behavior of the cemented tailings backfill under blast loading. A modified smooth surface cap model is consequently developed to characterize the yield of the material, which also facilitates hysteresis and full compaction as well as dilation control. Then, the viscoplastic formulation is further augmented with a variable bulk modulus derived from a Mie–Gruneisen equation of state, in order to capture the nonlinear hydrostatic response of cemented backfills subjected to high pressure. Subsequently, the material properties required in the viscoplastic cap model are coupled with a chemical model, which captures and quantifies the degree of cement hydration. Thus, the behavior of hydrating cemented backfills under the impact of blast loading can be evaluated under any curing time of interest. The validation results of the developed model show a good agreement between the experimental and the predicted results. The authors believe that the proposed model will contribute to a better understanding of the performance of cemented backfills under mine blasting and contribute to evaluating and managing the risk of failure of backfill structures under such a dynamic condition. Copyright © 2015 John Wiley & Sons, Ltd.